Two Faces of Naturalism: Thomas Hardy's jude the obscure and Émile Zola's germinal - Mikysková, Radka (Univerzita Pardubice, 2008)
The aim of this thesis is firstly to characterize the era when Naturalism appeared with focus on cultural and historic context. Therefore significant philosophical movements and scientific knowledge will be described in order to explain the general framework in which Naturalism emerged and which were its shaping factors. Secondly the analysis of primary sources is carried out, works of Hardy and Zola, two significant Naturalist writers, will be used. Specific issues significant for this literary movement such as genetic determination, Darwin’s Theory, psychological analysis of characters and influence of environment and circumstances will be discussed separately with focus on each of the two writers. This thesis will explain the possible influences of two naturalistic approaches, their similarities and differences.
Dvě tváře Naturalismu: Neblahý Juda Thomase Hardyho a Germinál Emila Zoly
Keywords: naturalismus; Émile Zola; Thomas Hardy; genetická determinace; psychologická analýza; sociální darwinismus; naturalism; genetic determination; psychological analysis; Social Darwinism